The dobutamine stress test as an alternative to exercise testing after acute myocardial infarction. Issue 5 (May 1988) - Mannering, D; Cripps, T; Leech, G; Mehta, N; Valantine, H; Gilmour, S; Bennett, E D
Abstract : Three weeks after myocardial infarction in 50 patients the effect of the infusion of a graded dose of dobutamine was compared with that of symptom limited treadmill exercise testing. The following variables were measured: blood pressure, heart rate, ST segment changes, Doppler aortic blood flow, and cross sectional echocardiographic dimensions. The heart rate and double product increased more during exercise than during dobutamine infusion, while maximum acceleration in the ascending aorta increased more during dobutamine infusion than during exercise. Significant ST depression was recorded in 22 patients during exercise and in 24 during dobutamine infusion; the concordance between the two tests was 88%. In all cases in which ST segment depression occurred in both tests the site of ST depression was the same. Dobutamine stress testing is an alternative to exercise testing in patients after myocardial infarction.